Construção e validação de uma hipermídia educativa sobre punção venosa periférica - Frota, Natasha Marques (2012)
The computing resources in nursing education is a reality that has intensified in recent years. The educational hypermedia on venipuncture (PVP), used in this study, it is an information technology and communication (ICT) built to assist nursing students in this subject. Thus, realizing the importance of educational tools in nursing education, was held this study with the following objectives: build a hypermedia educational about venipuncture to aid the teaching of nursing experts validate the content and technical aspects hypermedia educational, and evaluate the acquisition of knowledge of nursing students about venipuncture before and after use of hypermedia. This is a methodological research, applied production technology. Among the different methodologies for the development of ICT in virtual learning environments, we decided in this study, the methodology Galvis-Panqueva due to its clarity and cohesion with the purposes and objectives of the research. Thus, the five phases of this research are: analysis, design, development, evaluation and administration. Within these steps, this study included the construction, evaluation and validation of hypermedia. The analysis was limited objectives, content, target audience, the study environment and technology infrastructure. In the design phase was evaluated environment, interface and navigation structure of the hypermedia. The development consists in the materialization of any drawing prepared in the previous phase, being chosen programs like Flash and Shockwave, to perform the interactive effects and the selection of the programming language. Conducted three phases of construction of hypermedia, was released on the same platform SOLAR and then went through the evaluation process, which was divided into two stages: expert validation and evaluation for nursing students. In the validation process, were invited according to predetermined criteria, twenty-two skilled nursing and twenty two computer to evaluate hypermedia. The experts have made some suggestions in order to adapt the educational material. So after making the changes requested hypermedia became valid. Then, an assessment was made with nursing students, where we applied a pretest with ten objective questions regarding PVP. The students took the course through the hypermedia and after completion, answered the post-test. The findings of this evaluation revealed statistically significant results, since after the use of hypermedia students had higher scores on the successes and post-test on the subject of PVP. It is noticed that the use of these technologies is an important tool for the dissemination of information on the subject of venipuncture, in addition to supporting nursing education with the use of ICT within the academy, assisting the teacher in student learning and providing new strategies to complement classroom teaching.